2020
DOI: 10.1007/s12072-020-10055-9
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of occult HBV infection in immunized children with HBsAg-positive parents: a hospital-based analysis

Abstract: Background and object The risk of occult HBV infection (OBI) in children whose mothers are HBV carriers has received more widespread attention, but there were few reports to focus on the children with HBsAg-positive parents. In this study, we aimed to investigate the prevalence of OBI in immunized children with HBsAg-positive parents. Methods HBV-vaccinated Chinese hospitalized children with HBsAg-positive parents were analyzed in our investigation. Eligible subjects were tested using a standard nested PCR for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…In Iran, among street children, HB-sAg positive, HBsAb, HBcAb, and HCV-Ab were reported to be 3%, 26.6%, 8%, and 3.5%, respectively (37). However, the findings of the current research do not support the previous research (30,31). The results are consistent with previous studies for HCV infection; however, they are completely different for HBsAg and HBsAb (36).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In Iran, among street children, HB-sAg positive, HBsAb, HBcAb, and HCV-Ab were reported to be 3%, 26.6%, 8%, and 3.5%, respectively (37). However, the findings of the current research do not support the previous research (30,31). The results are consistent with previous studies for HCV infection; however, they are completely different for HBsAg and HBsAb (36).…”
Section: Discussioncontrasting
confidence: 58%
“…In Nigeria, a rate of 10% was reported for HBsAg-positive preschool children (29). In China, the OBI-positive rate was 3.1% (10/327), and the HBV-DNA rate was 14.1% (46/327) among HBV-vaccinated children with HBV-infected parents (30). In Japan, OBI (1.3%) was reported among immunized children with HBV carrier mothers (31).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated anti‐HBs OBI has been reported in vaccinated infants aged 6–98 months born to chronically infected mothers 10–12,14,22 . HBV DNA levels were consistently low, but often only transiently persistent beyond 1–4 years of age when follow‐up was available 11,13,23 .…”
Section: Discussionmentioning
confidence: 99%
“…In China and South East Asia, isolated anti‐HBs were reported in 6.3%–20.3% of immunocompetent blood donors with OBI 2,7–9 . Isolated anti‐HBs OBI has been also reported in immunized neonates born to HBsAg‐positive mothers and children with HBsAg‐positive parents 10–14 . When available, follow‐up of vaccinated children in these studies was relatively limited in time and often showed low and transient HBV DNA levels 11,13 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation